Awareness of Periodontal Disease and Motivation for Periodontal Treatment among the Irular Population in Cuddalore – A Cross Sectional Study - S. Sakthi Devi; G. K. Divyapriya; Prajot Raut; J. Monika; R. Saravana Kumar; K. Srinivasan (Current Overview on Disease and Health Research Vol. 9, 2023)
Irula, are Dravidians inhabiting the Indian states of Tamil Nadu, Kerala and Karnataka. Their population in this region is estimated at around 200, 000 people. The Irula people ethnicity are called Irular, and speak Irula, which belongs to the Dravidian. Traditionally, the main occupation of the Irulas has been snake catching and honey collection. The study aims to assess the oral hygiene practices, and awareness of periodontal diseases and treatments among the irular population in Cuddalore. The irular population of their irular colony were enrolled in the study and were provided with a questionnaire study consisting questions related to oral hygiene practices, awareness and the subjects were assessed for oral health knowledge based on it. The results of the study are educational status 53.6% Illiterates, Occupation 56.4% Unskilled workers, Income 97% < 1865, Brushing mode 94% use tooth brush, Frequency of brushing 49.1% once, Method of brushing 43.6% horizontal, Types of tooth paste 50% non – medicated , Other oral hygiene aids 81.8% no usage of other aids . Our study population clearly demonstrates that 89% of the Irular population had poor knowledge about various aspects of periodontal health and oral hygiene practices.